A note on the Laplace operator for holomorphic functions on complex Lie groups - IONESCU , Alexandru (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this note we obtain the local expression of the Laplace operator acting on holomorphic functions defined on a complex Lie group. Also, some applications to the theory of holomorphic last multipliers are given. Mathematics Subject Classification (2010): 22E10, 32M05, 53B20, 53B21, 53C56, 34A26.